THE EFFECTIVENESS OF GOVERNMENT SUBSIDIES AND LOW-COST FINANCING SCHEMES IN EQUALISING ACCESS TO LAND REGISTRATION - Gunawan Widjaja (Adisam Publisher, 2025)
This study aims to examine the effectiveness of government subsidies and low-cost financing schemes in supporting equitable access to land registration in Indonesia. The approach used is a literature review, collecting and analysing various scientific sources, regulations, and reports related to land policy. The results of the study show that government subsidies, particularly through the Complete Systematic Land Registration (PTSL) programme, significantly reduce the cost of land registration, thereby increasing the number of certificates issued to low-income communities. On the other hand, low-cost financing schemes offer a flexible alternative by providing easy instalment payments and low interest rates, thereby reaching communities that have difficulty accessing direct subsidies. These two instruments complement each other in expanding access to land registration, but their successful implementation is highly dependent on transparency, bureaucratic management, public financial literacy, and adequate regulatory support. This study recommends that subsidy and low-cost financing policies be managed in an integrated manner to ensure fair, inclusive, and sustainable access to land ownership.